Social Movements and the Politics of Debt: Transnational Resistance against Debt on Three Continents - Christoph Sorg (Amsterdam University Press, 2022)
It would have been hard to miss the pivotal role debt has played for contentious politics in the last decades. The North Atlantic Financial Crisis, Global Recession and European Debt Crisis - as well as the recent waves of protest that followed them - have catapulted debt politics into the limelight of public debates. Profiting from years of fieldwork and an extensive amount of empirical data, Christoph Sorg traces recent contestations of debt from North Africa to Europe and the US. In doing so, he identifies the emergence of new transnational movement networks against the injustice of current debt politics, which struggle for more social and democratic ways of organizing debt within and between societies.
Keywords: 330; Debt; financialization; contentious politics; social movements